Non-stationary response of photorefractive crystal under an external sinusoidal electric field - O. Salas-Torres (Revista Mexicana de Física, 2012)
We calculated the non-stationary holographic current arising in a photorefractive crystal illuminated by a vibrating sinusoidal pattern along with an external sinusoidal electric field applied to the sample. We first solved numerically the set of nonlinear material rate differentialequations to find the full overall space charged field and the mobile carrier density for a photorefractive BSO crystal. With these results we calculated the photocurrent, which is found to be in good agreement with corresponding values obtained from holographic experimentsperformed with similar samples.